Exercise increases pressure pain tolerance but not pressure and heat pain thresholds in healthy young men. (5th June 2016) - Vaegter, H.B.; Hoeger Bement, M.; Madsen, A.B.; Fridriksson, J.; Dasa, M.; Graven‐Nielsen, T.
Abstract: Background: Exercise causes an acute decrease in the pain sensitivity known as exercise‐induced hypoalgesia (EIH), but the specificity to certain pain modalities remains unknown. This study aimed to compare the effect of isometric exercise on the heat and pressure pain sensitivity. Methods: On three different days, 20 healthy young men performed two submaximal isometric knee extensions (30% maximal voluntary contraction in 3 min) and a control condition (quiet rest). Before and immediately after exercise and rest, the sensitivity to heat pain and pressure pain was assessed in randomized and counterbalanced order. Cuff pressure pain threshold (cPPT) and pain tolerance (cPTT) were assessed on the ipsilateral lower leg by computer‐controlled cuff algometry. Heat pain threshold (HPT) was recorded on the ipsilateral foot by a computer‐controlled thermal stimulator. Results: Cuff pressure pain tolerance was significantly increased after exercise compared with baseline and rest ( p < 0.05). Compared with rest, cPPT and HPT were not significantly increased by exercise. No significant correlation between exercise‐induced changes in HPT and cPPT was found. Test–retest reliability before and after the rest condition was better for cPPT and CPTT (intraclass correlation > 0.77) compared with HPT (intraclass correlation = 0.54). Conclusions: The results indicate that hypoalgesia after submaximal isometric exercise is primarily affecting tolerance of pressure pain compared with the pain threshold. These data contribute to the understanding of how isometric exercise influences pain perception, which is necessary to optimize the clinical utility of exercise in management of chronic pain. Significance: The effect of isometric exercise on pain tolerance may be relevant for patients in chronic musculoskeletal pain as a pain‐coping strategy. What does this study add?: The results indicate that hypoalgesia after submaximal isometric exercise is primarily affecting tolerance of pressure pain compared with the heat and pressure pain threshold. These data contribute to the understanding of how isometric exercise influences pain perception, which is necessary to optimize the clinical utility of exercise in management of chronic pain.